2018
DOI: 10.1111/jphp.12880
|View full text |Cite
|
Sign up to set email alerts
|

CB1 cannabinoid receptor ligands augment the antidepressant-like activity of biometals (magnesium and zinc) in the behavioural tests

Abstract: The simultaneous modulation of the cannabinoid system and supplementation of magnesium or zinc produce at least additive antidepressant-like effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…They also enhanced the antidepressant-like properties of biometals (i.e. magnesium, 10 mg/kg and zinc, 5 mg/kg) inhibiting the glutamatergic neurotransmission [12]. Additionally, Kruk-Słomka et al [10] reported that all of the CB receptor ligands used in the present experiments augmented the anti-immobility effects of anticholinergic scopolamine (0.3 mg/kg) in the murine FST.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…They also enhanced the antidepressant-like properties of biometals (i.e. magnesium, 10 mg/kg and zinc, 5 mg/kg) inhibiting the glutamatergic neurotransmission [12]. Additionally, Kruk-Słomka et al [10] reported that all of the CB receptor ligands used in the present experiments augmented the anti-immobility effects of anticholinergic scopolamine (0.3 mg/kg) in the murine FST.…”
Section: Discussionsupporting
confidence: 57%
“…Mice from the control groups were injected with either 1% aqueous solution of Tween and/or saline. The pre-treatment schedules and the tested doses were chosen on the basis of the literature data [10] and our previous experimental projects [6,11,12]. A standard volume of liquid dosage forms (i.e.…”
Section: Drugsmentioning
confidence: 99%
“…For example, non-endocannabinoid N-acylethanolamines found in many plants were found inactive for cannabinoid receptors, but nevertheless effective as restorative modulating lipid precursors that modify chronic inflammation in various infective, metabolic, and autoimmune states [ 107 ]. Functional interactions between the endocannabinoid system and essential ion micronutrient ions such as zinc and magnesium may be additive as it was shown in the animal models of depression [ 108 ].…”
Section: Other Dietary Interventions That Target Ecsmentioning
confidence: 99%
“…For instance, administrations of the inverse agonist CB 1 cannabinoid receptor, rimonabant, induces symptoms of anxiety and depression and even suicidal ideation [ 58 - 60 ]. Conversely, antidepressive effects have been found by using CB 1 cannabinoid receptor antagonists [ 61 - 63 ]. In line with the current pharmacological findings, mice lacking the CB 1 cannabinoid receptor display abnormal patterns at different behavioral paradigms associated with mood disorders.…”
Section: The Modulatory Role Of the Endocannabinoid System In Mental ...mentioning
confidence: 99%